Coupled effects of anthropogenic nutrient sources and meteo-oceanographic events in the trophic state of a subtropical estuarine system. (30th September 2019) - Cabral, Alex; Fonseca, Alessandra
Abstract: This study investigated how the biogeochemical processes and water quality of Madre's Estuarine System (MES) are influenced by different environmental conditions and nutrient runoff from a poor-regulated watershed. We applied the Land-Ocean Interactions in the Coastal Zone (LOICZ) model to estimated water and nutrient fluxes and the net ecosystem metabolism. The closest region to agriculture, the inner estuary, showed hypoxic and anoxic conditions, nutrients maxima in the bottom waters and organic enrichment in the sediment. In contrast, lower nutrients concentrations and oxic waters were found in the middle estuary, where autotrophic conditions predominated. The system's trophic state was directly correlated with the volume of precipitation, wind intensity and depth. The water column was oligotrophic and predominantly composed by freshwater during rainfall events. Southerly winds forced the intrusion of coastal waters into the estuary, increasing water column stratification, both physical and chemical, and the trophic state. This study demonstrated that nutrient runoff from the irrigate rice culture and untreated sewage are boosting symptoms of eutrophication. Also, the high turbidity levels might be replacing phytoplankton species by an opportunistic macrophyte. The low water residence time was an important mechanism to improve the water quality, exporting elevated nutrients loads to the continental shelf. Highlights: Anthropogenic nutrient runoff is fueling eutrophication in a subtropical estuary. The trophic state was directly correlated with rainfall and wind patterns. Water column stratification increased trophic conditions. The low residence time was a key mechanism for improving water quality.